Nickel Electroplating on 3D Printed Polylactic Acid (PLA) for Hardness Enhancement - Ragaventrand, Ramses Maur; Saptaji, Kushendarsyah; Setiawan, Iwan; Handayani, Murni; Fernandez, Nikolas Krisma Hadi (Journal of Applied Sciences and Advanced Technology, 2025)
Electroplating is a process that uses electric current to deposit a layer of metal onto the surface of a conductive material, enhancing its properties such as corrosion resistance, electrical conductivity, and mechanical strength. This study investigates the process of nickel electroplating on 3D-printed polylactic acid (PLA) substrates, focusing on the efficiency and quality of the nickel coatings achieved through electroplating techniques. The methodology encompasses several stages, starting with the design and 3D printing of PLA specimens. Following this, the preparation of the electroplating setup is meticulously carried out, ensuring optimal conditions for the electroplating process. The quality of the nickel coating is then evaluated through a series of tests to assess its mechanical and electrical properties. The key findings from this research indicate that the electroplating process effectively deposits nickel onto the PLA substrates. This deposition significantly enhances the mechanical strength and electrical conductivity of the PLA specimens. The study's results suggest that nickel electroplating on PLA can be a viable method for improving the material properties of 3D-printed parts. This advancement not only contributes to the development of cost-effective and sustainable metal coating techniques for polymer-based materials but also has the potential to broaden the application scope of 3D-printed parts in various fields of engineering and technology. Such improvements could be particularly beneficial in industries requiring enhanced material performance, such as electronics, automotive, and aerospace sectors.